Application of Chemical and Organic Fertilizers and Possible Effects in the Greenhouses of Mediterranean Region - ATILGAN, A.; COSKAN, A.; ALAGOZ, T.; OZ, H. (Asian Journal of Chemistry, 2010)
A number of survey studies was conducted in 56 villages of Adana, Mersin and Antalya provinces between 2005-2007 with the aim of determining the amounts of chemical and organic fertilizers applied and in order to check their possible effects both on environmental pollution and human health in the Mediterranean region where 83 % of Turkey's greenhouse production is performed. In order to determine the number of farms to be surveyed, Simple random sampling method was used. The number of farms to be surveyed was determined as 223 with a confidence limit of 95 % and a margin of error of 5 %. The relations between the variables were examined with a correlation analysis. The results obtained have demonstrated that 33 % of the farms apply N + P2O5 + K2O more than 50 kg da-1. This fertilizer amount is approximately 7 folds of Turkey's average. It has been seen that producers are not aware of the possible effects of the excessive use of mineral fertilizers and it has been identified that farms which use organic fertilizers, apply less amounts of mineral fertilizers. It has been concluded that agricultural pesticide and fertilizer dealers in the region have a great influence on producers and these people whose commercial aims are of primary importance, make the producers apply fertilizers without considering its necessity. Therefore, it is determined that 76 % of the producers apply fertilizers to their soils without any soil or plant analysis. According to correlation analysis, increasing education level of producer increased the number of producer that applies organic matter while decreased the number of farmers who use higher dose of fertilizer. It has seen that producers, who have knowledge of organic fertilizers, apply more organic fertilizers than the other producers in their greenhouses. Moreover, a negative relationship has been identified between education level and the level of chemical fertilizer application. The organic fertilizer users have mostly preferred the farmyard manure.